Strategic analysis of human resources management in its work to enhance organizational performance in the telecommunications sector, Kingdom of Saudi Arabia - Al-Shuwaikhat, Sadiq Ali; Al Tuwaym, Haya Ibrahim; Al-Dawsari, Sara Saad (Journal of Economic, Administrative and Legal Sciences, 2024)
Human resources management strategies are among the basics for achieving the goals of any company. Therefore, this research aimed to track and analyze the strategies and vision of human resources management for organizations in the Kingdom, addressing all aspects of recruitment and development for employees, from the recruitment processes themselves to the control of employment contracts, and in view of the ongoing challenges in the internal environments. It has become necessary for external and external organizations in the Kingdom to adopt modern methods. Therefore, this research analyzed resource management strategies to enhance organizational performance, and this is through the descriptive analytical approach to determine the main community features of the research, as the sample population included all workers in telecommunications sector companies in the Kingdom. data for the study. A questionnaire was distributed among the samples through social media to employees of telecommunications companies in the Kingdom, who numbered (220). The study reached a set of results, including: the presence of a high level of organizational performance in companies. The telecommunications sector in the Kingdom by members of the study sample, where the arithmetic mean value was 3.964 with a standard deviation of 0.888.It was found that the greater the level of application of recruitment and recruitment strategies by 1%, the greater the level of organizational performance. In the telecommunications sector companies in the Kingdom of Saudi Arabia, it amounted to 1.637%, which demonstrates the validity of the first sub-hypothesis of the study.
Keywords: Human Resource Management; Management Strategies; Organizational Performance